Comparative Production Performance and Rumen Bacterial Diversity of Fattening Beef Cattle Supplemented with Different Levels Concentrated Feed - Changze Han; Xinqiang Zhu; Kai Chen; Xiaoli Wang; Feifan Leng; Yonggang Wang; Shaowei Li (BioResources, 2024)
The production performance and rumen bacterial diversity were compared for different silage-based diets supplemented with common concentrate or bio-concentrate to develop an alternative of common concentrate for fatten cattle feeding. The daily gain of fattening cattle was increased by 0. 99 kg and 1.04 kg, respectively, when fed with single corn silage or mixed silage-based diet supplemented with bio-concentrate. There was no significant difference in water loss rate and cooked meat rate among groups (P>0.05), but the tenderness of beef in the bio-concentrate group was significantly higher than that in the common concentrate group (P<0.05). There were no adverse effects on beef quality and blood biochemical indexes in each group. Compared with the normal concentrate group, the OTU number and α-diversity index of rumen microorganisms of fattening cattle fed with mixed silage as the basic diet supplemented with bio-concentrate increased significantly. At generic level, the relative abundances of Prevotella, Porphyromonadaceae (unclassified), and Succiniclasticum were increased by adding bio-concentrate in the diets based on mixed silage and single sorghum silage. Relative abundances of Bacteroidetes (unclassified), Ruminococcaceae (unclassified), and Firmicutes (unclassified) decreased. In conclusion, the bio-concentrate might be a better choice than common concentrate for beef cattle breeding.